Measurement of Depth of Seabed and Sea Flow Rate Under SuraMadu Bridge Madura Side for Determination of Mooring Turbine Construction Sea Power Plants - Rizal, Nandiko (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
SuraMadu bridge as one of the bridge on Madura have a strategic function. Due to the rapid population growth on Madura, the people require a strategic and cheap electricity for industrial development especially in the region of Surabaya and Madura. The purpose of measuring the depth of the seafloor and ocean currents on strait of Madura is to know the contour of the seabed and the speed of ocean currents around the masts of the SuraMadu bridge of Madura. To measure the depth of a seabed and the ocean currents at a various points from SuraMadu Bridge are required to predict the characteristics of the ocean. The results showed the depth of the waters and the speed of ocean currents in the research area around the SuraMadu bridge ranges from 12 meters up to 15 meters with sea current velocity between 0.3 m/s² up to 1.6 m /s². The research method used the case study method. This research is conducted covering activity of location survey. Furthermore, bathymetry data analysis and processing bathymetry data analysis are performed.